(untitled) (Research, Society and Development, 2023)
Opportunistic infections represent a serious public health problem, especially in patients with immunodeficiency caused by HIV. If not treated properly, these infections can be serious and even fatal. The objective of this study is to report the case of a patient with a late diagnosis of HIV, who presented opportunistic infections. This is a clinical report of a 36-year-old bisexual man who was admitted to the hospital with symptoms of anorexia, rectal pain, abdominal pain and severe anemia. During his admission, it was discovered that he was infected with HIV and also had opportunistic infections, including esophageal candidiasis, HPV and CMV. After receiving a series of therapies, the patient showed significant improvement, with resolution of the initial symptoms and control of opportunistic infections, so he was referred for follow-up on an outpatient basis. Although the patient showed improvements in his condition, it is crucial to emphasize that his participation in the study revealed irreversible damage in terms of prevention. For years, he inadvertently transmitted the HIV virus, putting a significant number of people at risk. This highlights the critical challenge that delay in HIV diagnosis poses to controlling the epidemic.